Tourism product development - 3G E-Learning LLC (New York, NY 3G E-Learning LLC, 2023)
"Tourism organizations (whether in the public sector or the private sector) which ignore the need for a continuing stream successful new products risk being overtaken by more marketing -oriented competitors. The process of new product development (NPD) is logically no different in tourism than in other industries. However, the circumstances of tourism and the nature the product itself affect how NPD in tourism has to take place. Although there are limits to the ways in which classic marketing research techniques, developed for NPD in the fast moving consumer goods industries, can be employed in tourism. There are many stages of product development, but they all begin with identifying a need in the marketplace. Developing products that are tailored to visitors' needs will improve the profitability of the tourism business. Today, it is very important to have an online presence. Nearly all your potential visitors will do their travel research online through their computers, smartphones, or tablets. Visitors will check out potential tourism destinations, products, and services before arriving at a destination. In this book, you will learn all about product development and how it can support the growth of the tourism business." --
Introduction to tourism industry --Tourism products -- Tourism destination product development -- Cruises -- Sustainable tourism development -- Tourism marketing and advertising -- Religious and cultural tourism product -- Accessible tourism -- Index
Editorial board: Aleksandar Mratinkovic, Dan Piestun, Hazem Shawky Fouda, Felecia Killings, Dr. Sandra El Hajj, Fozia Parveen, Igor Krunic, Dr. Jovan Pehcevski, Dr. Tanjina Nur, Stephen and Michelle.
Includes bibliographical references and index.
Keywords: Tourism -- Management; Tourism -- Planning; Tourism -- Marketing; Sustainable tourism